Caracterização da fauna de flebotomíneos (diptera: psychodidae) no sul de Santa Catarina, Brasil - Variza, Paula Fassicolo (2016)
Leishmaniasis is a zoonotic disease caused by protozoan parasites of the genus Leishmania spp.. The transmission of leishmaniasis occurs by the bites of infected female sandfly. Studies of clinical, biological and epidemiological characterization are fundamental for the development of individualized action and prevention strategies for leishmaniasis, since the transmission patterns, species of Leishmania vectors and species may present very differently in different regions. Thus, the constant monitoring of circulating sandfly species is extremely important since, if they perceive the increase of species or specimens over the years, one must consider the establishment of control methods for these vectors. This study had as a goal to identify the phlebotomine fauna, as for its abundance (in peri-domiciliary, woods, animal food source) monthly flow and the molecular identification of Leishmania species in three cities of southern Santa Catarina, Brazil. The collecting of the insects occurred in the cities of Criciuma, Imaruí and Tubarão, where three collecting points were set in each city: animal food source, woods and peri-domiciliary. In order to collect the insects, it was used CDC light traps. There were monthly collections from April 2015 to march 2016 passing through the four seasons of the year, giving a total of 108 collections, where 4.200 insects of the family Psychodidae were collected. There was the presence of two subfamilies: Sycoracinae and Phlebotominae. The subfamily Sycoracinae is the one with the highest number of specimens collected, 4.193, while the subfamily Phlebotominae 7 specimens of two species: Nyssomyia neivai and Pintomyia fischeri. The cities of Imaruí and Tubarão were where there was the presence of sand flies, being the habitat more frequently near the peri-domiciliary .The females sand flies went through molecular analysis in order to detect the presence of protozoa of the genus Leishmania spp., however, the samples were negative.